IMPLIKASI BUY NOW PAY LATER (BNPL) PADA PERILAKU KONSUMTIF GENERASI Z DALAM PERSPEKTIF EKONOMI ISLAM - Venotty Ananda Putri; Lisana Tartila; Ananditha Nadya; Nabila Sari (Taksasila Edukasi Insani, 2025)
The swift advancement of digital technology has introduced financial innovations like Buy Now, Pay Later (BNPL). This payment method has become particularly popular among Generation Z, largely due to its promise of convenience and flexibility in online shopping.However, the widespread adoption of BNPL raises major concerns, especially regarding its implications for Generation Z's consumer behavior when viewed from an Islamic economic perspective. These concerns include impulse buying, the risk of excessive and unproductive debt accumulation, and potential conflicts with core Islamic principles such as the avoidance of waste and the prohibition of riba (interest). To mitigate these issues, it's crucial to improve financial literacy among Generation Z. We also need to ensure more transparency from BNPL providers, implement stricter regulations, and encourage responsible money management in line with Islamic principles.Keywords: Buy Now Pay Later, Generation Z, Islamic Economy